Strategi Pengelolaan Operasional untuk Meningkatkan Keuntungan dan Mengurangi Pengeluaran dalam Industri Daur Ulang Plastik - Ikhbar, Samsul; Nelly, Nelly; Maksalmina, Maksalmina; Amni, Chairul; Arsyad, Arsyad; Aulia Fansuri, Ahmad (Jurnal Serambi Engineering, 2025)
The plastic recycling industry holds significant potential to reduce environmental impact and create new economic value. However, this industry faces challenges such as high production costs, process inefficiencies, and increasing sustainability demands. This article discusses operational management strategies, including the implementation of lean manufacturing, IoT-based smart technologies, and circular economy principles. Lean manufacturing focuses on waste reduction and efficiency improvement, while IoT enables real-time data analysis to detect and resolve inefficiencies. The adoption of circular economy principles demonstrates a reduction in the use of new raw materials, production costs, and waste. The findings reveal that combining these strategies enhances operational efficiency, reduces expenditures, and supports environmental sustainability. This article provides recommendations for the plastic recycling industry to innovate continuously in addressing global challenges